Facile microwave synthesis of Zinc Ferrite@NCDs for photocatalytic degradation of fluoroquinolone antibiotics - Kaushal, Neha; Sarraf, Sonu; Basu, Aviru Kumar; Mishra, Sunita; Saha, Avishek (Materials Chemistry and Physics, 2024)
Zinc ferrite (ZnFe2O4) composites have attracted growing interest in photocatalytic water purification. Herein, the hybrids of zinc ferrite and nitrogen-doped carbon dots (ZnF@x%NCDs) were synthesized via facile micro-wave synthesis. X-ray diffraction and Raman characterization confirm the formation of the spinel structure, and elemental composition has been analyzed by X-ray photoelectron spectroscopy. The photocatalytic activity of ZnF@x%NCDs was evaluated via the decomposition of ciprofloxacin and norfloxacin under visible light illumination. We noted that 20 % weight loading of NCDs led to the highest (similar to 79.2 %) ciprofloxacin (CIP) degradation. Diffuse reflectance measurements demonstrate the reduction of the band gap in composites ZnF@20%NCDs (1.91 eV) compared with bare ZnF (2.03 eV); moreover, the hybridization of zinc ferrites with NCDs results in enhanced photocurrent density and surface area. The effect of experimental parameters, including the role of photocatalyst dosage, pH value, and initial concentration of pollutants on the degradation of CIP, have also been investigated.
Keywords: Carbon dots; Ciprofloxacin degradation; Norfloxacin degradation; Photocatalysis; Zinc Ferrite

Novel GO hoisted SnO2-BiOBr bifunctional catalyst for the remediation of organic dyes under illumination by visible light and electrocatalytic water splitting - Dhillon, Manshu; Naskar, Abhishek; Kaushal, Neha; Bhansali, Shekhar; Saha, Avishek; Basu, Aviru Kumar (NANOSCALE, 2024)
Keywords: Chemistry; Multidisciplinary; Nanoscience & Nanotechnology

Visible light-assisted ferro-photocatalytic application of bismuth ferrite nanoparticles synthesized at low temperature - Sarraf, Sonu; Kaushal, Neha; Chugh, Vibhas; Sundar, Adhiraj; Saha, Avishek; Basu, Aviru K. (Journal of Materials Science, 2024)
Polycrystalline nano-sized multiferroic bismuth ferrite was prepared by facile sole-gel method using acetic acid as a chelating agent followed by calcination at 450, 500, and 600 degrees C. Transmission electron spectroscopy and X-ray diffraction patterns revealed the crystallinity in the samples, and the crystallite size increased with calcination temperature. The calcination temperature also greatly influenced the grain size of the materials, and high calcination temperature induces a decline in the total surface area per unit mass of material. The ferroelectric polarization measurement showed a decrease in remnant polarization from 0.18 to 0.09 mu C/cm2 with an increase in temperature. The remnant polarization induced delayed recombination of charge carriers upon light illumination, and the high surface area led to the highest photocatalytic activity in 450 degrees C calcined samples. The higher photocurrent density in low-temperature calcined samples supports the visible-light photodegradation studies of Congo Red (CR) dye. A maximum of 76.6% photocatalytic activity was observed in the 450 celcius calcined bismuth ferrite samples. In summary, the higher photocatalytic efficiency in the low-temperature samples is attributable to the synergistic effect of relatively higher remnant polarization and higher surface area.

Enhanced mid-visible light absorption and long-lived charge carriers in an electronically and structurally integrated BiVO4-TiO2 photoanode for efficient artificial photosynthesis applications - Jha, Vikas Kumar; Salgaonkar, Kranti N.; Saha, Avishek; Gopinath, Chinnakonda S.; Iyer, E. Siva Subramaniam (Nanoscale, 2025)
The ever-increasing demand for sustainable solutions for eliminating environmental pollutants, solar energy harvesting, water splitting, etc. have led to the design and development of novel materials to achieve the desired result. In this regard, structurally and electronically integrated (SEI) BiVO4-TiO2 (SEI-BVT) with abundant heterojunctions has emerged as a promising entity for efficient charge separation, which in turn enhances artificial photosynthesis (APS) activity. The present work adopted a unique synthetic strategy using SILAR to fabricate SEI-BVT from ionic precursors (Bi3+ and VO43-) into the pores of TiO2, exhibiting benchmark APS efficiency compared to the individual components. This preparation results in approximately 180 trillion uniformly distributed heterojunctions in 1 mg cm-2 of the SEI-BVT photoanode material. Charge carriers in SEI-BVT and BiVO4 are similar; however, the recombination is highly hindered when SEI-BVT heterojunctions are formed in the former. Our earlier work demonstrated 31-38% solar-to-fuel efficiency (STFE) with BiVO4-TiO2 for APS in the presence of the Pd-nanocube co-catalyst. The emphasis of the current work is to explore the dynamics of the light-induced processes in these heterojunctions to understand the interfacial charge transfer process. Femtosecond transient absorption (TA) spectroscopy has been employed to monitor the excited state dynamics. Our results show that new trap states have evolved under light illumination, which are significantly long-lived and hinder charge recombination, and consequently enhance STFE. A significantly large number of charge carriers exhibit a lifetime of >> 6 ns with visible light photons, at least up to 720 nm, which is higher than the band-gap absorption onset at 490 nm for SEI-BVT compared to bulk BiVO4. The rate of formation of charge carriers is significantly affected in the heterojunctions.

Oxidase-like nanozyme activity of ultrathin copper metal–organic framework nanosheets with high specificity for catechol oxidation - Singh, Ajit Kumar; Sharma, Deepika; Singh, Devesh Kumar; Sarraf, Sonu; Basu, Aviru Kumar; Ganesan, Vellaichamy; Saha, Avishek (ChemCatChem, 2025)
In nature, catechol oxidase catalyzes the oxidation of o-diphenol to o-quinone to produce a series of highly important polyphenolic natural products. Although mimicking the functionality of natural enzyme using a nanozyme was found to be beneficial, attaining a high specificity is challenging. Herein, we have explored the thickness-dependent oxidase activity and specificity of Cu-metal-organic framework (MOF) nanosheets. The unique synthetic method offers control over the thickness of the Cu-MOF nanosheets. The ultrathin (4 nm) Cu-MOF (Cu-UMOF) nanosheets as an oxidase nanozyme exhibit high specificity for catechol oxidation without having any peroxidase activity. Interestingly, the thicker (20–30 nm) Cu-MOF nanosheets showed poor catechol oxidase and peroxidase activity. The binuclear Cu-center, coordinative, and electronic unsaturation tuned electronic structure in Cu-UMOF, resulting in higher specificity for catechol oxidation than thicker Cu-MOF.

Synthesis of Pd-integrated carbon Dot@TiO2 thin film for photocatalytic glycerol reforming reaction for producing hydrogen - Abraham, Athira; Salgaonkar, Kranti N.; Nivedhitha, Thazhath R.; Ekal, Vishal Ashok; Kondhekar, Deepali; Chakraborty, Shubhankar; Gopinath, Chinnakonda S.; Saha, Avishek (Chemistry-an Asian Journal, 2025)
A series of thin-film photocatalysts comprising TiO2 modified with carbon dots (CDs) dispersed either with palladium (Pd-CD/TiO2) or nickel (Ni-CD/TiO2) were synthesized via solid-state and wet-impregnation methods. Morphological characterization (HR-TEM, SEM-EDS) confirmed the anatase phase of TiO2 and the atomic dispersion of metal-integrated CDs on its surface. UV-vis DRS and XPS analyses revealed a marginal red shift in band-gap and the presence of sp2-hybridized graphitic carbon, and metal-carbon interactions, indicating enhanced light absorption and charge separation through Schottky junctions. Under direct sunlight illumination, Pd-CD/TiO2 thin film exhibited superior hydrogen yield (1167 mu mol g-1 h-1) and maintained stability over 25 h, outperforming Ni-CD/TiO2 (494 mu mol g-1 h-1) and bare TiO2 (166 mu mol g-1 h-1) photocatalyst thin films. Concurrent glycerol oxidation at neutral pH (pH similar to 7) yields glycolaldehyde (41% selectivity), formic acid, and dihydroxyacetone as value-added products. Enhanced photocurrent density and lower impedance of Pd-CD/TiO2 corroborate improved charge carrier separation and dynamics. The results demonstrate that Pd-CD synergistically improves the photocatalytic performance of the Pd-CD/TiO2 for sustainable hydrogen generation and selective biomass valorization.
Keywords: Glycerol oxidation; Graphitic carbon dots; hydrogen production; Photocatalysis; titania

Visible-light-driven photocatalytic glycerol oxidation to value-added and highly selective glyceric/lactic acid - Kulkarni-Sambhare, Mukta; Salgaonkar, Kranti N.; Saha, Avishek; Gopinath, Chinnakonda S. (ChemiCatChem, 2025)
Achieving economical and sustainable artificial photosynthesis (APS) in direct sunlight for liquid fuel production with high efficiency remains an important challenge. A major obstacle in the photoelectrochemical (PEC) oxidation of organic compounds is attaining high selectivity with the desired product(s). This study introduces a novel strategy by integrating BiVO4 quantum dots (BVQDs), structurally and electronically, into the nanopores of commercial TiO2 (BVT for BVQDs integrated in pores of TiO2) to improve solar-driven photocatalysis. The band gap of the BVT photoanode decreases to 2.53 eV as compared to pure TiO2 (3.2 eV), which enhances visible light absorption and charge separation. BVT with Pt as a co-catalyst acts as an APS system, which selectively oxidizes glycerol into lactic acid (100% selectivity at 1 mM glycerol) and glyceric acid (98% selectivity at 100 mM), while simultaneously generating green hydrogen. Selectivity of the product can be further controlled by anaerobic or aerobic conditions as well as the length of the reaction time. Direct integration of BVQDs into TiO2 mesopores significantly enhances charge separation as well as utilization at redox sites. Current work provides key insights into optimizing photocatalytic conditions for highly selective value-added chemical production, which highlights the sustainability and efficacy of TiO2-based semiconductors with quantum dot integration.
Keywords: energy conversion; Energy storage; Photocatalysis; Quantum material; solar energy

Concurrent glycerol oxidation and hydrogen production on Ce-Co oxide/carbon for sustainable biomass valorization - Jana, Jayasmita; Chowdhury, Somnath; Saha, Avishek; Kang, Sung Gu; Hur, Seung Hyun; Gopinath, Chinnakonda S. (Chemical Engineering Journal, 2026)
Integrating glycerol oxidation with water electrolysis offers a sustainable route for hydrogen production while enabling concurrent generation of industrially relevant C1-C3 value-added materials. This system replaces kinetically sluggish oxygen evolution reaction (OER) simultaneously delivering H-2 at the cathode with high turnover frequency, thereby lowering the overall cell voltage and enabling the valorization of glycerol, a major by-product of the biodiesel industry. However, the development of an efficient bifunctional electrocatalysts capable of driving cathodic as well as anodic half-cell reactions remains a key challenge. Herein, we present a cerium-cobalt oxide composite modified with an amorphous carbon layer (Ce,Co-O/C) as an effective bifunctional catalyst for glycerol-assisted water electrolysis. The interfacial electron distribution across the Co-Ce oxide heterojunction generated abundant redox-active sites and accelerates reaction kinetics, while the conductive carbon layer facilitates rapid charge transfer and imparts improved stability. Consequently, the Ce, Co-O/C catalyst exhibited high formate selectivity at 1.4 V (vs RHE) at room temperature and delivers a low cell voltage of 1.90 V at 100 mA cm(-2) in a symmetric Ce,Co-O/C vertical bar vertical bar Ce,Co-O/C system, maintaining operational stability over 100 h. This work provides a promising interface-engineering for designing self-supported bifunctional electrocatalysts toward integrated biomass assisted co-electrolysis systems.
Keywords: Amorphous carbon; biomass valorization; electrocatalysis; energy conversion; green hydrogen

Photoluminescence decay lifetime study of hydrothermally synthesized highly porous ruthenium-silica composite for optical dissolved oxygen sensing application - Hattale, Gangadhar; Kadam, Rutuja; Virole, Vishal; Pandya, Rinu; Paul, Aditya; Kumar, Ajay; Shevate, Rahul; Vanka, Kumar; Saha, Avishek; Kanawade, Rajesh (ACS Applied Nano Materials, 2026)
Pore size and surface area of photoluminescence (PL)-based transition metal composites play crucial roles in facilitating oxygen diffusion, thereby enhancing the response and sensitivity of optical dissolved oxygen (DO) sensors. In this study, we successfully applied the hydrothermal method to synthesize a porous ruthenium composite embedded in a silica matrix, demonstrating its effectiveness for optical DO sensing applications. The ruthenium-silica (Ru-Si) composites were synthesized using Ru(bpy)3 2+ and tetraethyl orthosilicate (TEOS) as precursors, with reaction temperatures ranging from 120 degrees C to 200 degrees C over a fixed duration of 4 h. The structural, morphological, and compositional characterization techniques confirmed the successful synthesis and evaluated the porosity, surface features, and chemical structure of the resulting composites. The optimized Ru-Si composite exhibited the highest porosity, characterized by a specific surface area of 996.78 m2 g- 1, and exhibited the highest decay lifetime of 8.14 mu s in deionized (DI) water, compared to other composites. Importantly, we demonstrate an excellent linear response of the synthesized Ru-Si composite to DO concentrations ranging from 2.58 to 11.16 mg L-1, with a Stern-Volmer constant of 0.12. Furthermore, a density functional theory study was conducted to investigate the electronic transitions and to elucidate the oxygen quenching mechanism of the excited Ru composite with molecular oxygen. The calculated photophysical parameters of the composite show good agreement with the experimental results. Preliminary results suggest that the synthesized Ru-Si with high pore size and surface area could be an efficient and effective composite for use in DO sensing applications.
Keywords: Hydrothermal method; opticalDO sensor; oxygen quenching; photoluminescent; ruthenium composite

Polysulfone-based polymer carbon dot membrane for optical dissolved oxygen sensing application - Kadam, Rutuja; Hattale, Gangadhar; Virole, Vishal; Pal, Sanjivani; Abraham, Athira; Paul, Aditya; Kumar, Ajay; Shevate, Rahul; Banpurkar, Arun; Kanawade, Rajesh; Saha, Avishek (Chemistry-An Asian Journal, 2026)
The precise monitoring of dissolved oxygen (DO) is essential across industrial, environmental, and biomedical applications. However, the state-of-the-art DO sensing methods often suffer from inherent limitations, which hinder their effectiveness for real-time and long-term DO monitoring. Optical DO sensing, despite its advantages, utilizes expensive metal complexes and is prone to photobleaching and slow response time. Here, we introduce a novel polymer carbon dot (PCD) as a promising candidate for lifetime-based optical DO sensing. The PCD is a metal-free, nontoxic, fluorescent, long decay-lifetime material that is synthesized through hydrothermal method. Our fluorescent PCD exhibits high emission quantum yield (24.32%), long decay-lifetime (10.43 & micro;s), and a linear response to DO concentrations ranging from 0.7 to 12.7 mg/L, with a Stern-Volmer constant of 0.1115. Further, to obtain better oxygen diffusion, high porosity, optical transparency, and high flexibility, PCD was embedded into a polysulfone matrix (PSF_PCD). The PSF_PCD membrane shows better results for the decay lifetime (9.4 & micro;s), surface energy (40.26 mN/m), and average pore diameter of 5 nm. Hence, the obtained results demonstrate the applicability of the PCD in optical DO sensors for real-time and long-term monitoring of DO levels.
Keywords: decay lifetime; dissolved oxygen; Hydrothermal method; polymer carbon dots; polysulfone-based membrane